A Systematic Review of Coronavirus Disease 2019 Vaccine Efficacy and Effectiveness Against Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Disease. (18th April 2022) - Higdon, Melissa M; Wahl, Brian; Jones, Carli B; Rosen, Joseph G; Truelove, Shaun A; Baidya, Anurima; Nande, Anjalika A; ShamaeiZadeh, Parisa A; Walter, Karoline K; Feikin, Daniel R; Patel, Minal K; Deloria Knoll, Maria; et al.
Abstract: Billions of doses of coronavirus disease 2019 (COVID-19) vaccines have been administered globally, dramatically reducing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) incidence and severity in some settings. Many studies suggest vaccines provide a high degree of protection against infection and disease, but precise estimates vary and studies differ in design, outcomes measured, dosing regime, location, and circulating virus strains. In this study, we conduct a systematic review of COVID-19 vaccines through February 2022. We included efficacy data from Phase 3 clinical trials for 15 vaccines undergoing World Health Organization Emergency Use Listing evaluation and real-world effectiveness for 8 vaccines with observational studies meeting inclusion criteria. Vaccine metrics collected include protection against asymptomatic infection, any infection, symptomatic COVID-19, and severe outcomes including hospitalization and death, for partial or complete vaccination, and against variants of concern Alpha, Beta, Gamma, Delta, and Omicron. We additionally review the epidemiological principles behind the design and interpretation of vaccine efficacy and effectiveness studies, including important sources of heterogeneity. Abstract : We conduct a systematic review of COVID-19 vaccine efficacy and effectiveness through February 2022. This synthesis includes 15 vaccine products and covers protection against infection and disease for multiple SARS-CoV-2 variants, for partial and complete primary vaccination series.